Recent revolutions in biology - Corrick, James A. (New York : F. Watts, 1987)
Surveys new theories, discoveries, and realms of inquiry in biology, discussing evolution, gene therapy, genetic engineering, life on other planets, and other topics.
Includes index.
Keywords: Biology -- Juvenile literature; Biology